Kewenangan dan Pertanggungjawaban Notaris dalam Proses Pembentukan Perseroan Terbatas - Mochammad Ibrahim Syam Rizki (Pusat Riset dan Inovasi Nasional, 2025)
A notary plays a strategic role in the process of establishing a Limited Liability Company (PT) as a public official authorized to create authentic deeds. This authority is regulated under the Notary Office Act (UUJN) and the Limited Liability Company Act (UUPT), which stipulate that the deed of establishment of a PT must be made in the form of an authentic deed by a notary. This study aims to analyze the notary’s authority in the process of establishing a PT as well as the forms of legal liability that arise in the event of errors or negligence. The research method used is a normative juridical approach by examining legislation, doctrines, and relevant court decisions. The findings show that the notary’s authority is an attribution granted directly by law, and therefore its exercise must comply with legal procedures. A notary’s liability may be civil, criminal, or administrative if proven to have committed a violation, whether intentional or due to negligence. Thus, a notary does not merely function as a formal intermediary in the establishment of a PT but also as a guarantor of legal certainty for the parties involved. This study emphasizes the importance of professionalism and integrity of notaries in maintaining public trust and ensuring legal protection in the practice of establishing PTs.